Single-layer temporary bonding material and preparation method and application thereof

By compounding thermoplastic resin containing photosensitive groups with auxiliary resin and compatibilizer, a single-layer temporary bonding material is prepared, which solves the problems of cumbersome operation and low-energy debonding in the existing technology, realizes efficient and low-cost laser debonding, and prevents damage to the wafer during the packaging process.

CN120795524APending Publication Date: 2025-10-17SHENZHEN SAMCIEN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510907791.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing temporary bonding materials are difficult to meet the multi-faceted requirements of laser debonding, especially when achieving laser debonding at low energy thresholds. The operation is cumbersome and cannot effectively prevent warping or breakage of ultra-thin wafers due to mechanical and thermal stress during the packaging process.

Method used

A thermoplastic resin containing photosensitive groups is used as the main resin, which is compounded with auxiliary resin and compatibilizer to form a single-layer temporary bonding material. It has high temperature resistance, solvent corrosion resistance and good mechanical properties, and can achieve laser debonding at low energy.

Benefits of technology

It provides a single-layer temporary bonding material with simple operation and low cost, which can achieve laser debonding at a low energy threshold, is suitable for mass production, prevents wafer fragmentation during the grinding and polishing process, and improves the stability and reliability of the wafer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795524A_ABST
    Figure CN120795524A_ABST
Patent Text Reader

Abstract

The invention relates to a single-layer temporary bonding material and a preparation method and application thereof. The single-layer temporary bonding material comprises components of main body resin, auxiliary material resin and a compatibilizer; the matrix resin is thermoplastic resin containing a photosensitive group. The single-layer temporary bonding material provided by the invention has excellent high temperature resistance, solvent corrosion resistance, oxidation resistance and the like, has the advantages of simplicity in operation and lower cost when being used for a temporary bonding process, and can also well achieve the purpose of laser de-bonding under a low energy threshold.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of laser temporary bonding, in particular to a single-layer temporary bonding material and a preparation method and application thereof. BACKGROUND

[0002] With the feature size of integrated circuit manufacturing process continuously shrinking, and the introduction of advanced packaging technology represented by three-dimensional integration, the wafer in electronic components is getting thinner and thinner, and the thickness of a single wafer needs to be reduced to 100 μm or even thinner. These ultra-thin wafers will be warped or broken during packaging due to mechanical and thermal stress and other factors. In order to prevent these damages, a certain specific intermediate layer material is usually used to temporarily bond the ultra-thin wafer to a wafer carrier before packaging, and this process is called temporary bonding process.

[0003] The temporary bonding process includes bonding and debonding. The key difference between temporary bonding and permanent bonding lies in the debonding process. The debonding process includes thermal release debonding, chemical release debonding, laser debonding, mechanical release debonding, etc. Among them, laser debonding is a stress-free debonding method, which principle is to use laser irradiation to cause photodecomposition of the polymer adhesive, reduce the viscosity and separate from the interface. Its advantages include room temperature operation, no stress, fast debonding speed, and suitable for mass production.

[0004] However, it is difficult for a single-layer material to meet the multi-directional requirements of laser debonding glue in the temporary bonding process. At present, the temporary bonding glue used for laser debonding includes two layers of materials, namely, an adhesive layer and a release layer. The adhesive layer is coated on the surface of the functional wafer, and the release layer is coated on the transparent glass carrier. The design of the two layers of materials makes the bonding, debonding and cleaning steps more complicated.

[0005] Therefore, it is of great significance to develop a single-layer temporary bonding material for laser release, which has the properties of high temperature resistance, polarity solvent corrosion resistance, and can provide good mechanical properties for wafer thinning, and can also achieve laser debonding at a low energy threshold. SUMMARY

[0006] To solve the above technical problems, the present application provides a single-layer temporary bonding material and a preparation method and application thereof. The single-layer temporary bonding material has excellent properties of high temperature resistance, solvent corrosion resistance and oxidation resistance. When used in the temporary bonding process, it has the advantages of simple operation and low cost, and can also achieve the purpose of laser debonding at a low energy threshold.

[0007] To achieve this purpose, the present application adopts the following technical solutions:

[0008] In a first aspect, the present application provides a single-layer temporary bonding material, which comprises components of a main resin, an auxiliary resin and a compatibilizer; the main resin is a thermoplastic resin containing a photosensitive group.

[0009] The components of the temporary bonding material are designed in the present application, and by matching the thermoplastic resin containing a photosensitive group as the main resin with the auxiliary resin and the compatibilizer, the properties of photosensitivity and support are ingeniously integrated, and a single-layer temporary bonding material with excellent comprehensive properties such as mechanical properties, resistance to chemical and high-temperature properties is obtained.

[0010] In the present application, the thermoplastic resin containing a photosensitive group is matched as the main resin with the auxiliary resin, so that the two can play a synergistic effect, thereby improving the stability of the obtained single-layer temporary bonding material, and further making it have excellent high-temperature resistance and resistance to corrosion of polar solvents; at the same time, the obtained single-layer temporary bonding material also has good mechanical strength, and the uneven stress phenomenon does not occur in the processing process, which can provide sufficient support force for the wafer to prevent the wafer from breaking and other risks in the grinding and polishing process. In addition, the thermoplastic resin containing a photosensitive group has strong absorption properties to ultraviolet laser, so that the single-layer temporary bonding material obtained by taking it as the main resin in the present application can well realize the effect of low-energy ultraviolet laser release debonding.

[0011] The following is a preferred technical solution of the present application, but is not a limitation on the technical solutions provided by the present application. Through the following preferred technical solution, the purpose and beneficial effects of the present application can be better achieved and realized.

[0012] As a preferred technical solution of the present application, the single-layer temporary bonding material comprises the following components with mass percentage:

[0013]

[0014] In the single-layer temporary bonding material of the present application, the mass percentage of the main resin can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42% or 45%, the mass percentage of the auxiliary resin can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22% or 25%, the mass percentage of the compatibilizer can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8% or 2%, and the mass percentage of the solvent can be 40%, 45%, 50%, 55%, 60%, 65%, 70% or 74.9%, and the specific point values between the above point values. Due to the consideration of space and simplicity, the present application does not exhaustively list the specific point values included in the range.

[0015] As a preferred technical scheme of the present application, the mass percentage of the main resin in the single-layer temporary bonding material is 25-35%, for example, it can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, and specific point values between the above point values. Due to the limitation of the length and the consideration of simplicity, the present application does not list all the specific point values included in the range.

[0016] In the present application, the thermoplastic resin containing a photosensitive group is used as the main resin of the material system, which is the main component for forming the single-layer temporary bonding material. It not only has the properties of oxidation resistance, strong acid and alkali resistance, and polar solvent resistance, but also has the properties of strong absorption of ultraviolet laser, and can further play the role of low-energy ultraviolet laser debonding. By optimizing the mass percentage of the main resin, the obtained single-layer temporary bonding material has good thermal stability, solvent corrosion resistance and good laser responsiveness. When the mass percentage is low, the obtained single-layer temporary bonding material has low absorption capacity for laser, and is prone to laser debonding failure, which makes it difficult to achieve good laser debonding effect. When the mass percentage is high, the thermal stability and chemical resistance (oxidation resistance, strong acid and alkali resistance, and polar solvent resistance) of the obtained single-layer temporary bonding material are poor, especially the solvent corrosion resistance is reduced, and the mechanical properties are also deteriorated.

[0017] As a preferred technical scheme of the present application, the mass percentage of the auxiliary resin in the single-layer temporary bonding material is 10-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, and specific point values between the above point values. Due to the limitation of the length and the consideration of simplicity, the present application does not list all the specific point values included in the range.

[0018] In the present application, the addition of auxiliary resin can improve the system stability of the obtained single-layer temporary bonding material and improve its rheological properties. By optimizing the mass percentage of the auxiliary resin, it can be well compounded with the main resin, so that the obtained single-layer temporary bonding material has good thermal stability, solvent corrosion resistance and good laser responsiveness. When the mass percentage is low, the chemical resistance (oxidation resistance, strong acid and alkali resistance, and polar solvent resistance) of the obtained single-layer temporary bonding material is insufficient; when the mass percentage is high, it is prone to laser debonding failure, and the cleaning effect is poor, and the mechanical properties are also deteriorated.

[0019] Preferably, the main resin is prepared by free radical polymerization reaction of a thermoplastic resin and a monomer containing a photosensitive group.

[0020] Preferably, the thermoplastic resin is a thermoplastic resin containing unsaturated bonds.

[0021] Preferably, the thermoplastic resin containing unsaturated bond comprises SIS resin and / or SBS resin.

[0022] Preferably, the photosensitive group comprises azobenzene group.

[0023] Preferably, the monomer containing photosensitive group comprises acrylamide monomer containing azobenzene group and / or acrylate monomer containing azobenzene group.

[0024] Preferably, the acrylamide monomer containing azobenzene group is obtained by condensation of acyl chloride containing carbon-carbon double bond with aminoazobenzene.

[0025] Preferably, the acyl chloride containing carbon-carbon double bond comprises acryloyl chloride and / or methacryloyl chloride.

[0026] Preferably, the aminoazobenzene comprises any one of 4,4'-diaminoazobenzene, 4-amino-4'-dimethylaminoazobenzene, 4-amino-4'-methylaminoazobenzene, 2,3-difluoro-4-aminoazobenzene, 4-((4-aminophenyl)azo)benzoic acid ethyl ester, 4-aminoazobenzene, 4-amino-4'-diethylaminoazobenzene, 4-amino-4'-ethylaminoazobenzene or 4-amino-4'-hydroxyaminoazobenzene or a combination of at least two thereof.

[0027] Preferably, the acrylate monomer containing azobenzene group is obtained by condensation of acyl chloride containing carbon-carbon double bond with hydroxyazobenzene.

[0028] Preferably, the hydroxyazobenzene comprises any one of 4-hydroxyazobenzene, phenylazo-2-naphthol or solvent red 23 or a combination of at least two thereof.

[0029] Preferably, the host resin is prepared by a preparation method comprising the following steps:

[0030] The thermoplastic resin is mixed with the monomer containing photosensitive group, the temperature is set to 60-120℃, after adding organic solvent for heating and dissolving, initiator is added and reacted for 4-12h, after the reaction is completed, purification and drying are performed to obtain the host resin.

[0031] Preferably, the mass ratio of the thermoplastic resin to the monomer containing photosensitive group is 5:(1-15), wherein (1-15) can be 1, 3, 5, 7, 10, 12 or 15, and specific point values between the above point values, limited to the length and for the sake of simplicity, the present application does not exhaustively list the specific point values included in the range, and further preferably 5:(2.5-10).

[0032] Preferably, the initiator comprises an azo initiator and / or a peroxide initiator.

[0033] It should be noted that the present application does not have special limitations on the types of azo initiators and peroxide initiators, and the azo initiators and peroxide initiators commonly used in the art are all applicable. Exemplary azo initiators include, but are not limited to, azobisisobutyronitrile and azobisisoheptyl nitrile. Exemplary peroxide initiators include, but are not limited to, benzoyl peroxide, dilauroyl peroxide, and methyl tert-butyl benzene peroxide.

[0034] Preferably, the mass ratio of the initiator to the monomer containing a photosensitive group is 1:(2.7-20), where (2.7-20) can be, for example, 2.7, 3, 5, 7, 10, 12, 14, 16, 18, or 20, and specific point values between the above point values. Due to the limited space and the consideration of simplicity, the present application will not exhaustively list the specific point values included in the range.

[0035] Preferably, the organic solvent comprises any one or a combination of at least two of cyclohexanone, p-methylbenzene, limonene, ethylcyclohexane, toluene, mesitylene, dioxane, ethylene glycol methyl ether acetate, N,N-dimethylformamide, or N,N-dimethylacetamide.

[0036] Preferably, the mass percentage of the organic solvent in the reaction system is 25-81%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 81%, and specific point values between the above point values. Due to the limited space and the consideration of simplicity, the present application will not exhaustively list the specific point values included in the range.

[0037] Preferably, the purification method comprises dissolving and precipitating using an alcohol solvent.

[0038] Preferably, the alcohol solvent comprises any one or a combination of at least two of methanol, ethanol, or isopropanol.

[0039] Preferably, the drying method comprises drying under reduced pressure.

[0040] Preferably, the drying temperature is 25-80℃, for example, it can be 25℃, 30℃, 40℃, 50℃, 60℃, 70℃, or 80℃, and specific point values between the above point values. Due to the limited space and the consideration of simplicity, the present application will not exhaustively list the specific point values included in the range.

[0041] Specifically, the main resin is prepared by the following preparation method, which specifically comprises the following steps:

[0042] The thermoplastic resin and the monomer containing a photosensitive group are added to a jacketed reactor at a mass ratio of 5: (1-15), the temperature is set to 60-120℃, after being dissolved by adding an organic solvent and heating, a nitrogen-based initiator and / or a peroxide-based initiator are added, and the reaction is carried out for 4-12h, after the reaction is completed, the product is dissolved and separated using an alcohol solvent, and is dried at 25-80℃ under reduced pressure, to obtain the main resin.

[0043] Preferably, the auxiliary resin includes any one of or a combination of at least two of tetrakis (2, 6-dimethylphenyl) phenylene phosphate polycondensate, polystyrene, polyvinyl chloride, poly-1-butene, polyacrylonitrile, polyvinyl acetate, SEBS, ABS, SBS, MBS, styrene acrylic resin, acrylic-acrylic ether copolymer, acrylate-butyl glycol acrylate copolymer, or teracrylate copolymer.

[0044] Preferably, the styrene acrylic resin includes acrylate-styrene copolymer.

[0045] Preferably, the teracrylate copolymer includes acrylate-acrylate-styrene copolymer, etc.

[0046] Preferably, the compatibilizer includes any one of or a combination of at least two of maleic anhydride type styrene, maleic anhydride type butadiene, silicon-acrylic type compound, epoxy compound, polyvinyl alcohol, sodium xylene sulfonate, or polydimethylsiloxane.

[0047] Preferably, the epoxy compound includes glycidyl methacrylate.

[0048] In the present application, the use of the compatibilizer can enhance the compatibility of the main resin and the auxiliary resin, reduce the interfacial tension, and improve the dispersion, thereby improving the phase stability and the interfacial adhesion, and improving the adhesive filling effect, which is beneficial to improving the mechanical properties of the obtained single-layer temporary bonding material.

[0049] Preferably, the solvent includes any one of or a combination of at least two of ketone solvent, aromatic hydrocarbon solvent, ether solvent, amide solvent, dimethyl sulfoxide, or decalin, and further, the solvent is not more than three, for example, it can be one, a combination of any two, or a combination of any three.

[0050] Preferably, the ketone solvent includes any one of or a combination of at least two of acetone, butanone, cyclohexanone, or isophorone.

[0051] Preferably, the aromatic hydrocarbon solvent includes toluene and / or trimethylbenzene.

[0052] Preferably, the ether solvent includes any one of dioxane, 1,3-dioxolane, 2,2,4,4,5,5-hexamethyl-1,3-dioxolane, 2,2-dimethoxy-4-(trifluoromethyl)-1,3-dioxolane, tetrahydrofuran or fluorinated hexagonal coordination ether, or a combination of at least two thereof.

[0053] Preferably, the amide solvent includes dimethylformamide and / or N,N-dimethylacetamide.

[0054] In the present application, the solvent is mainly used to well dissolve and disperse the main resin and the auxiliary resin to form a dispersion system, and further, by adding the required auxiliary agent, it is beneficial to form a system with uniform dispersion and uniform composition. In addition, part of the components can also act as a glue solvent for diluting the material system with too high viscosity.

[0055] Preferably, the single-layer temporary bonding material further comprises a leveling agent.

[0056] In the present application, the use of leveling agent can reduce the surface tension of the obtained single-layer temporary bonding material, and well ensure the flatness and smoothness of the spin coating on the substrate, and improve the TTV (Total Thickness Variation).

[0057] Preferably, the mass percentage content of the leveling agent in the single-layer temporary bonding material is 0.05-1.5%, for example, it can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 1.2% or 1.5%, and specific point values between the above point values, limited to the length and for the sake of simplicity, the present application will not be exhaustively listed The specific point values included in the range are further preferably 0.2-1.0%.

[0058] Preferably, the leveling agent includes any one of acrylic leveling agent, fluorocarbon compound leveling agent or silicone leveling agent, or a combination of at least two thereof.

[0059] In a second aspect, the present application provides a preparation method of the single-layer temporary bonding material according to the first aspect, and the preparation method comprises the following steps:

[0060] Mixing the main resin, the auxiliary resin, the compatibilizer and the optional leveling agent to obtain the single-layer temporary bonding material.

[0061] Exemplarily, the preparation method of the single-layer temporary bonding material specifically comprises the following steps:

[0062] (1) The main resin and the auxiliary resin are added to the stirred tank and slowly stirred at 80-120 rpm;

[0063] (2) 60% of the solvent is added to the stirred kettle, the rotation speed is adjusted to 140-160 rpm, and stirring is performed for 3.5-4.5 h, and then the rotation speed is adjusted to 190-210 rpm, and stirring is performed for 3.5-4.5 h;

[0064] (3) the compatibilizer and the optional leveling agent are sequentially added to the stirred kettle, the remaining 40% of the solvent is used to flush the material on the inner wall of the stirred kettle into the stirred kettle to mix with other components, the rotation speed is adjusted to 240-260 rpm, and stirring is performed for 23-25 h;

[0065] (4) the rotation speed is adjusted to 290-310 rpm, and stirring is continued for 23-25 h; standing is performed for 23-25 h to obtain the glue;

[0066] (5) the glue in step (4) is sequentially filtered by using 5 μm, 1 μm and 0.45 μm filter cores to obtain the single-layer temporary bonding material.

[0067] In a third aspect, the present application provides a use of the single-layer temporary bonding material according to the first aspect in a temporary bonding process.

[0068] Preferably, the use method comprises the following steps:

[0069] S1: spin coating the single-layer temporary bonding material according to the first aspect on a substrate to obtain a substrate with a glue surface;

[0070] S2: curing the substrate with the glue surface in step S1 to obtain a sample coated with a temporary bonding layer;

[0071] S3: thermocompression bonding the sample coated with the temporary bonding layer in step S2 and a substrate material to obtain a bonded pair;

[0072] S4: debonding the bonded pair in step S3 to obtain a thin wafer.

[0073] In the present application, the material of the substrate is not particularly limited, and exemplary materials include, but are not limited to, AF35G Schott glass and sapphire substrate, preferably a transparent material close to the elastic modulus, the thermal expansion coefficient and the Poisson's ratio of the wafer to be bonded.

[0074] Preferably, the thickness of the spin coating in step S1 is 10-40 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm, and specific point values between the above point values. Due to the limited space and the consideration of simplicity, the present application does not list all the specific point values included in the range.

[0075] In the present application, the film thickness uniformity after spin coating is within 5%.

[0076] Preferably, the substrate of step S1 needs to be pre-processed before spin coating.

[0077] Preferably, the pre-processing step comprises treating the surface of the substrate with plasma to increase its surface roughness, thereby increasing the adhesion between the single layer of temporary bonding material and the substrate.

[0078] Preferably, the temperature of the curing of step S2 is 150-180°C, for example, it can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, and the specific point values between the above-mentioned point values, limited to the length and for the sake of simplicity, the present application will not be listed in the range of the specific point values included.

[0079] Preferably, the time of the curing of step S2 is 5-10min, for example, it can be 5min, 5.5min, 6min, 6.5min, 7min, 7.5min, 8min, 8.5min, 9min, 9.5min or 10min, and the specific point values between the above-mentioned point values, limited to the length and for the sake of simplicity, the present application will not be listed in the range of the specific point values included.

[0080] Preferably, the temperature of the thermal compression bonding of step S3 is 170-190°C, for example, it can be 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C, 184°C, 186°C, 188°C or 200°C, and the specific point values between the above-mentioned point values, limited to the length and for the sake of simplicity, the present application will not be listed in the range of the specific point values included.

[0081] Preferably, the pressure of the thermal compression bonding of step S3 is 900-1100N, for example, it can be 900N, 920N, 940N, 960N, 980N, 1000N, 1020N, 1040N, 4060N, 1080N or 1100N, and the specific point values between the above-mentioned point values, limited to the length and for the sake of simplicity, the present application will not be listed in the range of the specific point values included.

[0082] Preferably, the time of the thermal compression bonding of step S3 is 5-10min, for example, it can be 5min, 5.5min, 6min, 6.5min, 7min, 7.5min, 8min, 8.5min, 9min, 9.5min or 10min, and the specific point values between the above-mentioned point values, limited to the length and for the sake of simplicity, the present application will not be listed in the range of the specific point values included.

[0083] Preferably, the vacuum degree of the thermal compression bonding in step S3 is less than 10 Pa, for example, can be 0.1 Pa, 0.5 Pa, 1 Pa, 2 Pa, 3 Pa, 4 Pa, 5 Pa, 6 Pa, 7 Pa, 8 Pa or 9 Pa, and specific point values between the above-mentioned point values, for the sake of brevity and simplicity, the present application does not list the specific point values included in the range.

[0084] Preferably, after the thermal compression bonding in step S3 is completed, the wafer surface of the bonded pair is thinned and polished.

[0085] It should be noted that the present application does not make any special limitation on the type of substrate material in step S3, which can be adjusted according to actual needs, exemplarily including but not limited to silicon wafer.

[0086] Preferably, the debonding in step S4 is achieved by laser scanning.

[0087] In the present application, the wavelength band of the laser is not subject to any special limitation, including but not limited to 355 nm or 532 nm.

[0088] Preferably, the energy density of the laser is 200-500 mj / cm2, for example, can be 200 mj / cm2, 250 mj / cm2, 300 mj / cm2, 350 mj / cm2, 400 mj / cm2, 450 mj / cm2or 500 mj / cm2, and specific point values between the above-mentioned point values, for the sake of brevity and simplicity, the present application does not list the specific point values included in the range. 2 2 2 2 2 2

[0089] Preferably, the thin wafer in step S4 also needs to be cleaned with a cleaning agent.

[0090] The present application does not make any special limitation on the type of cleaning agent, exemplarily including but not limited to Remover 4.

[0091] Exemplarily, the applied method specifically includes the following steps:

[0092] S1: spin coating of temporary bonding material glue solution. Using a spin coater to spin coat a single layer of temporary bonding material with a thickness of 10-40 μm on a substrate (plasma treated) to obtain a substrate with a glue surface;

[0093] S2: place the substrate with the glue surface facing up on a baking oven, bake at 150-180°C for 5-10 min to solidify, then obtain a sample coated with a temporary bonding layer, and cool the sample to room temperature for standby use;​​​​​​

[0094] S3: using a wafer bonder, the sample described in step S2 is placed on the upper side, and the substrate material is placed on the lower side, and the hot-press bonding is performed at 170-190 DEG C, 900-1100 N, and a vacuum degree < 10 Pa for 5-10 min, to obtain a bonded pair;

[0095] S4: using a laser debonding device, the bonded pair described in step S3 is debonded to obtain a thin wafer, the light spot is close-packed, the light spot is considered to have no overlap, and the laser energy density is 200-500 mj / cm 2 .

[0096] Compared with the prior art, the present application has at least the following beneficial effects:

[0097] (1) The present application designs the components of the temporary bonding material, and by matching the thermoplastic resin containing a photosensitive group as the main resin with auxiliary resin and a compatibilizer, a single-layer temporary bonding material with excellent comprehensive performance such as mechanical properties, high-temperature resistance, and chemical resistance is obtained.

[0098] (2) Further, the single-layer temporary bonding material provided by the present application can be well applied to the temporary bonding process, has simple operation steps and low cost, can realize laser debonding at a low energy threshold, and is suitable for mass production. BRIEF DESCRIPTION OF DRAWINGS

[0099] Figure 1 is a flow chart of the temporary bonding process described in the present application. DETAILED DESCRIPTION

[0100] The technical solutions of the present application will be further described below by combining the drawings and through specific embodiments. However, the following examples are only simple examples of the present application, and do not represent or limit the protection scope of the present application, and the protection scope of the present application is subject to the claims.

[0101] The flow chart of the temporary bonding process described in the present application is exemplarily shown in Figure 1 .

[0102] The raw materials and solvents used in the following examples and comparative examples are all commercially available unless otherwise specified, and part of the raw material information is shown in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] Preparation Example 1

[0107] The preparation example provides a host resin 1, and a specific preparation method thereof includes the following steps.

[0108] 100 parts by weight of SIS resin and 50 parts by weight of 4-(phenylazo)phenyl methacrylate (CAS: 3774-20-7) are added to a jacketed reactor, the temperature is set to 80°C, 700 parts by weight of dioxane is added for heating and dissolution, then 18 parts by weight of azobisisobutyronitrile is added, and reaction is performed for 6 hours; after the reaction is completed, methanol is used for dissolution and precipitation, the obtained solid is dried under reduced pressure at -100 Kpa and 60°C, and the host resin 1 is obtained.

[0109] Preparation Example 2

[0110] The preparation example provides a host resin 2, and a specific preparation method thereof includes the following steps.

[0111] 100 parts by weight of SIS resin and 50 parts by weight of 4-(phenylazo)phenyl methacrylate (CAS: 3774-20-7) are added to a jacketed reactor, the temperature is set to 80°C, 700 parts by weight of dioxane is added for heating and dissolution, then 18 parts by weight of azobisisobutyronitrile is added, and reaction is performed for 6 hours; after the reaction is completed, methanol is used for dissolution and precipitation, the obtained solid is dried under reduced pressure at -100 Kpa and 60°C, and the host resin 1 is obtained.

[0112] Examples 1-5

[0113] Examples 1-5 respectively provide a single-layer temporary bonding material, which specifically includes components with mass percentages as shown in Table 2.

[0114] Table 2

[0115]

[0116]

[0117] The preparation method of the single-layer temporary bonding material in Examples 1-5 specifically includes the following steps.

[0118] (1) The host resin and the auxiliary resin are added to a 10L stirred tank, and stirring is slowly performed at 100 rpm;

[0119] (2) 60% of the solvent is added to the stirred tank, the stirring speed is adjusted to 150 rpm, and stirring is performed for 4 hours; then the stirring speed is adjusted to 200 rpm, and stirring is performed for 4 hours;

[0120] (3) The compatibilizer and the leveling agent are sequentially added to the stirred tank, and the remaining 40% solvent is used to flush the material on the inner wall of the stirred tank into the stirred tank to mix with other components, and the stirring speed is adjusted to 250 rpm, and stirring is performed for 24 h;

[0121] (4) The stirring speed is adjusted to 300 rpm, and after 24 h of continuous stirring, the stirring is stopped for 24 h, and a glue is obtained;

[0122] (5) The glue in step (4) is sequentially filtered using filter cores with pore sizes of 5 μm, 1 μm, and 0.45 μm, and a single-layer temporary bonding material is obtained.

[0123] Examples 6-17 and Comparative Example 1

[0124] Examples 6-17 and Comparative Example 1 each provide a single-layer temporary bonding material, the specific components and mass percentages thereof are shown in Table 3 (in “%” units), and other preparation methods are the same as those in Example 1.

[0125] Table 3

[0126]

[0127]

[0128] Comparative Example 2

[0129] This comparative example provides a single-layer temporary bonding material, which is different from Example 1 only in that the main resin 1 in Example 1 is replaced by an equal amount of polyvinyl cinnamate (purchased from Macklin, CAS: 9050-06-0), and other components, mass percentages, and preparation methods are the same as those in Example 1.

[0130] Application Example 1

[0131] This application example provides a temporary bonding process, and the method of the temporary bonding process specifically includes the following steps:

[0132] S1: A spin coater is used to spin coat the single-layer temporary bonding material obtained in Example 1 on a substrate (plasma-treated 8-inch AF35G Schott glass) to a thickness of 25 μm, and a substrate with a glue surface is obtained;

[0133] S2: The substrate with the glue surface up is placed on a flat support on a baking oven, and after baking at 165 °C for 8 min for curing, a sample coated with a temporary bonding layer is obtained, and the sample is cooled to room temperature for standby;

[0134] S3: A wafer bonding machine is used to place the sample in step S2 on top, and an 8-inch silicon wafer is placed below, and hot-press bonding is performed at 180 °C, 1000 N, and a vacuum degree of 0.1 Pa for 5 min, and a bonded pair is obtained.

[0135] S4: using a laser debonding device to debond the bonding pair described in step S3 to obtain a thin wafer, the laser wavelength is 355 nm, the light spot is dense arrangement, the light spot is considered to have no overlap, and the laser energy density is 300 mj / cm 2 .

[0136] Application Example 2

[0137] The temporary bonding process provided in this application example specifically includes the following steps:

[0138] S1: using a spin coater to spin coat the single-layer temporary bonding material obtained in Example 2 on a substrate (8-inch AF35G Schott glass subjected to plasma treatment) to obtain a substrate with a glue surface;

[0139] S2: place the substrate with the glue surface facing up on a flat holder on an oven, and after curing at 150°C for 10 minutes, obtain a sample coated with a temporary bonding layer, and cool the sample to room temperature for standby;

[0140] S3: using a wafer bonding machine, place the sample described in step S2 on top, and place an 8-inch silicon wafer (containing a 500μm edge trimming process) on the bottom, and perform hot-press bonding at 170°C, 1100N, and a vacuum degree of 0.1Pa for 10 minutes to obtain a bonding pair;

[0141] S4: using a laser debonding device to debond the bonding pair described in step S3 to obtain a thin wafer, the laser wavelength is 355 nm, the light spot is dense arrangement, the light spot is considered to have no overlap, and the laser energy density is 300 mj / cm 2 .

[0142] Application Example 3

[0143] The temporary bonding process provided in this application example specifically includes the following steps:

[0144] S1: using a spin coater to spin coat the single-layer temporary bonding material obtained in Example 3 on a substrate (8-inch AF35G Schott glass subjected to plasma treatment) to obtain a substrate with a glue surface;

[0145] S2: place the substrate with the glue surface facing up on a flat holder on an oven, and after curing at 180°C for 5 minutes, obtain a sample coated with a temporary bonding layer, and cool the sample to room temperature for standby;

[0146] S3: Use a wafer bonder to place the sample described in step S2 on top and an 8-inch silicon wafer (including a 500 μm edge trimming process) on the bottom, and perform hot-press bonding at 190°C, 900 N, and a vacuum of 0.1 Pa for 5 minutes to obtain a bonded pair;

[0147] S4: Use laser debonding equipment to debond the bonded pair described in step S3 to obtain a thin wafer. The laser wavelength is 355nm laser, the light spots are closely packed, and the light spots are considered to have no overlap. The laser energy density is 300mj / cm 2 .

[0148] Application Example 4-17 and Comparative Application Example 1-2

[0149] Application Examples 4-17 and Comparative Application Examples 1-2 respectively provide a temporary bonding process. The method of the temporary bonding process differs from that of Application Example 1 only in that the single-layer temporary bonding material obtained in Example 1 in Application Example 1 is replaced with the single-layer temporary bonding material obtained in Example 4-17 and Comparative Example 1-2. The operating steps of other methods are the same as those of Application Example 1.

[0150] The performance test methods / standards are as follows:

[0151] (1) Thinning and polishing test

[0152] Wafer thinning and polishing equipment is used to thin and polish the bonded silicon wafers to 50 μm. OM observation of edge cracking: 1 or fewer cracks or edge fragments, with no crack defects exceeding 3000 μm in linear length, are considered excellent; 3 or fewer crack defects are considered acceptable; and more than 3 crack defects or crack defects exceeding 3000 μm in linear length are considered unacceptable.

[0153] (2) Warpage test: After bonding, the warpage is tested using a wafer warpage tester (Keyence, IM-8000). A warpage of less than 100 μm is considered excellent, a warpage of 100-200 μm is considered good, and a warpage greater than 200 μm is considered poor.

[0154] (3) Curing high temperature process simulation test

[0155] The thinned bond pair is placed with the silicon surface facing up in an oven with a nitrogen atmosphere (oxygen content <100ppm), a heating and cooling rate of 5℃ / min, and maintained at 250℃ for 2h. The high-temperature process bond pair has no bubbles or cavities and the high-temperature resistance is excellent; the bond pair with a 1cm edge removal has a bubble or cavity with a wafer radial width less than 300μm in the middle, and no bubble or cavity with a wafer radial width greater than 300μm within 1cm of the edge is qualified; the bond pair with a 1cm edge removal has two or more bubbles or cavities with a wafer radial width less than 300μm in the middle, or no bubble or cavity with a wafer radial width greater than 300μm within 1cm of the edge is unqualified.

[0156] (4) Resistance to chemical performance test

[0157] Continue to soak the bonding pair with different reagents in turn, and soak in IPA at room temperature for 5 min each time. After IPA spray washing, dry. The resistance to chemical reagents and soaking conditions are as follows: 2.38% TMAH @ 25°C for 5 min, DMSO:DMF:TMAH (mass ratio of 87:10:3) @ 65°C for 5 min, acetone @ 25°C for 5 min, NMP:glycol @ 65°C for 5 min, PGME @ 25°C for 5 min, 30% HCl @ 25°C for 3 min, 30% NH4OH @ 25°C for 3 min, 10% H2SO4 @ 25°C for 3 min, SC1 (NH4OH:H2O2:H2O, mass ratio of 1:1:5) @ 75°C for 5 min, SC2 (HCl:H2O2:H2O, mass ratio of 1:1:6) @ 75°C for 5 min. Observe the corrosion of the bonding pair, and the resistance to chemical performance is excellent when the average corrosion depth is less than 200 μm, qualified when the average corrosion depth is 200-1000 μm, and poor when the average corrosion depth is greater than or equal to 1000 μm.

[0158] (5) Debonding effect test

[0159] During the debonding process, the pulling force after laser scanning is less than 50 N, and 1-3 scans are performed until the debonding is released. The debonding effect is excellent for one-time debonding, qualified for 2-3 times of debonding, and unqualified for 3 times or more or unable to debond.

[0160] (6) Cleaning effect test

[0161] The thin wafer is cleaned using Remover 4 (Shenzhen Huaxun Semiconductor Material Co., Ltd.), soaking for 1 min + 1000 rpm @ spraying for 1 min @ flow rate of 150-300 mL / min, and cleaning for 20 min. Isopropyl alcohol (IPA) is used to spray clean the wafer and blow dry. The wafer is scanned for particle size using an AOI scanning device, and the cleaning effect is excellent when the number of 0.2 μm*0.2 μm particles is less than 500 and the number of 2*2 μm particles is less than 30, qualified when the number of 0.2 μm*0.2 μm particles is less than 2000 and the number of 2*2 μm particles is less than 300, and unqualified in other cases.

[0162] The test results are shown in Table 4.

[0163] Table 4

[0164]

[0165]

[0166] From the test results, it can be seen that:

[0167] (1) Through application examples 1 to 17, it can be seen that by designing the components of the temporary bonding material, a single-layer temporary bonding material with excellent comprehensive performance such as mechanical properties, high-temperature resistance and chemical resistance is obtained, which can achieve laser debonding at a low energy threshold and has excellent cleaning effect when applied in the temporary bonding process.

[0168] (2) Through application examples 6-9, it can be seen that compared with application examples 7 and 8, the debonding effect of application example 6 is poor, the high-temperature resistance and chemical resistance of application example 9 are poor, and the degree of fragmentation and warpage are both increased, indicating that by optimizing the content of the main resin, the high-temperature resistance, chemical resistance and mechanical properties of the obtained single-layer temporary bonding material can be further improved, and the debonding effect in the temporary bonding process can be improved.

[0169] (3) Through application examples 10-13, it can be seen that compared with application examples 11 and 12, the chemical resistance of application example 10 is poor, the debonding and cleaning effect of application example 13 is poor, and the warpage is large, indicating that by optimizing the content of the auxiliary resin, the high-temperature resistance, chemical resistance and mechanical properties of the obtained single-layer temporary bonding material can be further improved, and the debonding and cleaning effect in the temporary bonding process can be improved.

[0170] (4) Through the comparison of application example 1 and comparative application example 1, it can be seen that comparative application example 1 does not add auxiliary resin, and the temporary bonding material obtained thereby can achieve excellent laser debonding and cleaning effect in the temporary bonding process, but its mechanical properties and high-temperature resistance and chemical resistance are not qualified, and it cannot be well applied in actual production, indicating that by compounding the main resin and the auxiliary resin, the two can play a good synergistic effect, thereby obtaining a single-layer temporary bonding material with excellent comprehensive performance, which can be well applied in the single-layer temporary bonding process.

[0171] (5) Through the comparison of application example 1 and comparative application example 2, it can be seen that comparative application example 2 uses a conventional resin, and the temporary bonding material obtained thereby has good mechanical properties, high-temperature resistance and chemical resistance, but it cannot achieve laser debonding effect at a low energy threshold, indicating that by specific selection of the main resin, the obtained single-layer temporary bonding material can maintain good mechanical properties, high-temperature resistance and chemical resistance, and also can achieve excellent laser debonding effect at a low energy threshold when applied in the temporary bonding process.

[0172] In summary, the application designs the components of the temporary bonding material, and by matching the thermoplastic resin containing a photosensitive group as a main body resin with auxiliary resin and a compatibilizer, the properties of photosensitivity and support are ingeniously integrated, and a single-layer temporary bonding material with excellent comprehensive properties such as mechanical properties, chemical resistance and high-temperature resistance is obtained, which can well realize laser debonding at a low energy threshold when applied in the temporary bonding process, and has excellent cleaning effect.

[0173] The applicant declares that the above is only a specific embodiment of the application, but the protection scope of the application is not limited thereto, and those skilled in the art should understand that any changes or replacements within the technical scope disclosed by the application, which can be easily thought of by any person skilled in the art, falls within the protection scope and disclosure scope of the application.

Claims

1. A single-layer temporary bonding material, characterized in that: The single-layer temporary bonding material comprises components of a main resin, an auxiliary resin and a compatibilizer; the main resin is a thermoplastic resin containing a photosensitive group.

2. The single-layer temporary bonding material according to claim 1, characterized in that The single-layer temporary bonding material includes the following components in percentage by mass:

3. The single-layer temporary bonding material according to claim 2, characterized in that The mass percentage of the main resin in the single-layer temporary bonding material is 25-35%; Preferably, the mass percentage of the auxiliary resin in the single-layer temporary bonding material is 10-20%.

4. The single-layer temporary bonding material according to any one of claims 1 to 3, characterized in that: The main resin is prepared by free radical polymerization of a thermoplastic resin and a monomer containing a photosensitive group; Preferably, the thermoplastic resin is a thermoplastic resin containing unsaturated bonds; Preferably, the unsaturated bond-containing thermoplastic resin includes SIS resin and / or SBS resin; Preferably, the photosensitive group includes an azobenzene group; Preferably, the monomer containing a photosensitive group includes an acrylamide monomer containing an azobenzene group and / or an acrylate monomer containing an azobenzene group.

5. The single-layer temporary bonding material according to any one of claims 1 to 4, characterized in that: The auxiliary resin includes any one or a combination of at least two of 1,3-phenylene tetrakis(2,6-dimethylphenyl)phosphate condensation product, polystyrene, polyvinyl chloride, poly-1-butene, polyacrylonitrile, polyvinyl acetate, SEBS, ABS, SBS, MBS, styrene acrylic resin, acrylic acid-acrylic ether copolymer, acrylate-butylene glycol acrylate copolymer or ternary acrylate copolymer.

6. The single-layer temporary bonding material according to any one of claims 1 to 5, characterized in that: The compatibilizer includes any one of maleic anhydride styrene, maleic anhydride butadiene, silicon-acrylic acid type compound, epoxy compound, polyvinyl alcohol, sodium xylene sulfonate or polydimethylsiloxane, or a combination of at least two thereof.

7. The single-layer temporary bonding material according to any one of claims 1 to 6, characterized in that: The single-layer temporary bonding material also includes a leveling agent; Preferably, the mass percentage of the leveling agent in the single-layer temporary bonding material is 0.05-1.5%; Preferably, the leveling agent includes any one of an acrylic leveling agent, a fluorocarbon leveling agent or an organosilicon leveling agent, or a combination of at least two thereof.

8. A method for preparing a single-layer temporary bonding material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The main resin, the auxiliary resin, the compatibilizer and the optional leveling agent are mixed to obtain the single-layer temporary bonding material.

9. Use of the single-layer temporary bonding material according to any one of claims 1 to 7 in a temporary bonding process.

10. The use according to claim 9, characterized in that The application method comprises the following steps: S1: spin coating a single layer of temporary bonding material according to any one of claims 1 to 7 on a substrate to obtain a substrate with an adhesive surface; S2: curing the substrate with the adhesive surface described in step S1 to obtain a sample coated with a temporary bonding layer; S3: performing thermal compression bonding on the sample coated with the temporary bonding layer and the substrate material in step S2 to obtain a bonding pair; S4: Debonding the bonded pair described in step S3 to obtain a thin wafer; Preferably, the spin coating thickness in step S1 is 10-40 μm; Preferably, the curing temperature in step S2 is 150-180°C.